2015
DOI: 10.1371/journal.pone.0141170
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomes from Egyptian Cattle Breeds: New Clues on the Origin of Haplogroup Q and the Early Spread of Bos taurus from the Near East

Abstract: BackgroundGenetic studies support the scenario that Bos taurus domestication occurred in the Near East during the Neolithic transition about 10 thousand years (ky) ago, with the likely exception of a minor secondary event in Italy. However, despite the proven effectiveness of whole mitochondrial genome data in providing valuable information concerning the origin of taurine cattle, until now no population surveys have been carried out at the level of mitogenomes in local breeds from the Near East or surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Complete mitogenome sequences were obtained by using two different approaches: 1) PCR amplification (with 27 primer pairs, Supplementary Table S2A) 40 and Sanger sequencing; 2) Long-Range PCR amplification (Supplementary Table S2B) and Illumina sequencing 41 . GenBank accession number, sequencing method, coverage and depth of each sample are reported in Supplementary Dataset S1.…”
Section: Methodsmentioning
confidence: 99%
“…Complete mitogenome sequences were obtained by using two different approaches: 1) PCR amplification (with 27 primer pairs, Supplementary Table S2A) 40 and Sanger sequencing; 2) Long-Range PCR amplification (Supplementary Table S2B) and Illumina sequencing 41 . GenBank accession number, sequencing method, coverage and depth of each sample are reported in Supplementary Dataset S1.…”
Section: Methodsmentioning
confidence: 99%
“…They thought the important factor of geographic structure of horse is geographic isolation by Silk Road, high mountain, and etc. In addition, geographic isolation of other domestic animals such as goat were reported [e.g., [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with recent reviews of genetic data suggestive of introgression of Y-chromosomal data from African Bos primigenius into African Bos taurus descended from Near Eastern stock (Achilli et al 2010;Bonfiglio et al 2012;Olivieri et al 2015;Perez-Pardal et al 2010;Stock and Gifford-Gonzalez 2013), a re-examination of the archaeobotanical, faunal and geomorphological data from the early and middle Holocene periods in the Nabta Playa-Bir Kiseiba region is appropriate in order to determine whether the ecological underpinnings of the early African independent domestication model are valid.…”
Section: Summary Of the Main Arguments To Date For And Against An Earmentioning
confidence: 99%
“…These and other studies (Ajmone-Marsan et al 2010, Beja-Pereira et al 2006 show that the T1 haplogroup found in African Bos taurus originates in the Fertile Crescent. Olivieri et al (2015) undertook Bayesian and phylogenetic analyses on 31 mitogenomes from the Domiatry and Menofi cattle breeds in the Nile Delta. High haplotype and haplogroup affiliation diversity were detected.…”
Section: Implications Of Haplotype Diversity For the Origins Of Domesmentioning
confidence: 99%